Everything Is Now : New and Collected Stories - Cliff, Michelle (Book collections on Project MUSE., 2009)
Everything Is Now brings together all the short fiction of Michelle Cliff, featuring fourteen new pieces as well as the stories from her two previous short fiction collections (Bodies of Water and The Store of a Million Items). Cliff, born in Jamaica and raised both there and in New York, skillfully weaves her own experiences into her fiction, exploring race, gender, sexuality, and colonialism. With stunning lyricism, intelligence, and passion, Cliff confronts the dualities of our complex world: black and white, America and the third world, past and present, femininity and masculinity, coloniali.